2019
DOI: 10.3844/ijrnsp.2019.1.9
|View full text |Cite
|
Sign up to set email alerts
|

An Examination of Factor Structure of the Hamilton Anxiety Rating Scale in a Non-Clinical Persian Sample

Abstract: The Hamilton Anxiety Rating Scale is an internationally used assessment tool for anxiety level however its acceptable factor structure remains fluid. The aim of this paper is to examine the psychometric properties and establish normative anxiety prevalence rates with a Persian randomized sample. A cross sectional survey was distributed to a randomised sample of adults (n = 1260) in the Middle East. A two-factor model was deemed the most statistically and theoretically appropriate measurement model. This repres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 39 publications
3
6
0
Order By: Relevance
“…Results of the factor analysis suggested that the SIGH-A yields a highly correlated two-factor solution with good internal consistency and item-test correlations, consistent with previous studies examining other versions of the Hamilton Scale in predominately White samples (Beck & Steer, 1991; Clark & Donovan, 1994; Hamilton, 1959; Slater et al, 2019). Despite these promising results, factor loadings were modest, and post hoc modifications, i.e., allowing error covariances between Items 11 (Gastrointestinal symptoms) and 14 (Behavior at interview), were recommended.…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations
“…Results of the factor analysis suggested that the SIGH-A yields a highly correlated two-factor solution with good internal consistency and item-test correlations, consistent with previous studies examining other versions of the Hamilton Scale in predominately White samples (Beck & Steer, 1991; Clark & Donovan, 1994; Hamilton, 1959; Slater et al, 2019). Despite these promising results, factor loadings were modest, and post hoc modifications, i.e., allowing error covariances between Items 11 (Gastrointestinal symptoms) and 14 (Behavior at interview), were recommended.…”
Section: Discussionsupporting
confidence: 85%
“…Despite these promising results, factor loadings were modest, and post hoc modifications, i.e., allowing error covariances between Items 11 (Gastrointestinal symptoms) and 14 (Behavior at interview), were recommended. While such recommendations to the two-factor solution are not unexpected in light of previous factor analytic studies using the Hamilton scale (i.e., Clark & Donovan, 1994; Slater et al, 2019), it is noteworthy that the error terms implicated in these post hoc modifications differ from those in previous studies, possibly suggesting that these changes are based on statistical improvements to the model rather than a priori theoretical bases (see MacCallum et al, 1992). Alternatively, the differential modifications to error terms across studies may signal that some of the Hamilton’s item content is not invariant across racial populations (i.e., that the constructs operationalized on the Hamilton scale have different meanings across racial groups; Kline, 2016), thus highlighting the importance of continued examination of the Hamilton scale among non-White samples.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…Studies validating the HAM-A in clinical populations (including OCD) have not assessed the factor structure systematically. Two-factor model for HAM-A similar to what we reported, was also found in a nonclinical Persian population (Slater et al, 2019), and in a alcoholism-PTSD comorbid sample (Marks et al, 2021) In our study, both the HAM-D and the HAM-A met configural invariance with acceptable RMSEA values, but did not meet the cutoff for metric invariance, indicating that items have different loadings between sites. One of the reasons for this could be the heterogeneity in the sample characteristics across the sites, with respect to the rates of comorbid MDD and anxiety disorders.…”
Section: Measures Of Depression and Anxietysupporting
confidence: 86%